Knowledge of malaria prevention and control methods and associated factors among rural households in west Belessa district, north west Ethiopia, 2019 - Tsigie Baye Aragie (BMC, 2020)
Abstract Background In Ethiopia malaria is one of the top ten leading causes of morbidity and mortality. Community knowledge of prevention and control methods had been proven to play an important role in the implementation of effective and sustainable interventions against malaria. This information is limited in the study area. This study aimed to assess knowledge of malaria prevention and control methods and its associated factors among households in West Belessa district, 2019. Methods Community-based cross-sectional mixed quantitative and qualitative study was conducted from April to June 2019 in West Belessa district, North West Ethiopia. Multistage sampling was used to select an estimated 770 sample size. A structured questionnaire was used for the quantitative component and semi-structured questionnaire for the qualitative component. Quantitative data were collected by interviewing and qualitative data using focus group discussion (FGD). Quantitative data was coded and entered using Epi info software version 7 then exported to SPSS version 20 for analysis. The binary logistic regression model was fitted to identify the associated factors. Odds Ratio (OR) with 95% Confidence Interval (CI) was used to assess the strength of association. The qualitative data was transcribed manually using the thematic approach. Result A total of 770 subjects were included in this study with a 99.5% response rate. Of the total respondents, 75.6% had good knowledge of malaria prevention methods. LLINs and IRS were mentioned by 84.7 and 83.7% respectively. Poorest wealth quintiles [AOR = 0.40, 95% CI: 0.23, 0.73], poor wealth quintiles [AOR = 0.38, 95% CI: 0.21, 0.70], and medium wealth quintiles [AOR = 0.41, 95% CI: 0.22, 0.76], living in Menti Kebele [AOR = 3.07, 95% CI 1.85, 5.08], living in Abay tera kebele [AOR = 2.00, 95% CI 1.21, 3.29] were significantly associated with good knowledge. About all of the focused group discussion (FGD) participants agreed that malaria is a preventable disease and mentioned some of the preventive methods. Conclusion Overall there was relatively high knowledge of malaria prevention and control methods. LLINs and IRS were known malaria prevention methods in West Belessa. Wealth index and respondents living kebele are predictors for knowledge of malaria prevention.